2014
DOI: 10.2478/raon-2013-0085
|View full text |Cite
|
Sign up to set email alerts
|

Post-mastectomy radiotherapy benefits subgroups of breast cancer patients with T1-2 tumor and 1–3 axillary lymph node(s) metastasis

Abstract: BackgroundTo determine the role of postmastectomy radiotherapy (PMRT) in breast cancer patients with T1–2 and N1 disease.Patients and methods.A total of 207 postmastectomy women were enrolled. The 5-year Kaplan-Meier estimates of locoregional recurrence rate (LRR), distant recurrence rate (DRR) and overall survival (OS) were analyzed by different tumor characteristics. Multivariate analyses were performed using Cox proportional hazards modeling.ResultsWith median follow-up 59.5 months, the 5-year LRR, DRR and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…location, HER2̸neu overexpression and negative oestrogen receptor status were associated with poorer outcomes and a reduction in OS (4)(5)(6)10,12). Higher-grade disease, a triple-negative subtype, age <40 years, HER2̸neu overexpression and negative oestrogen receptor status were all identified as independent poor prognostic factors for LRR (5,6,10,12,13). In order to fully elucidate the effect of these factors, and other factors, such as the use of systemic therapy, on the suggested LRR rates and OS when PMRT is used, future prospective randomised trials are warranted.…”
Section: Test a Resultsmentioning
confidence: 99%
“…location, HER2̸neu overexpression and negative oestrogen receptor status were associated with poorer outcomes and a reduction in OS (4)(5)(6)10,12). Higher-grade disease, a triple-negative subtype, age <40 years, HER2̸neu overexpression and negative oestrogen receptor status were all identified as independent poor prognostic factors for LRR (5,6,10,12,13). In order to fully elucidate the effect of these factors, and other factors, such as the use of systemic therapy, on the suggested LRR rates and OS when PMRT is used, future prospective randomised trials are warranted.…”
Section: Test a Resultsmentioning
confidence: 99%
“…The current international consensus does not recommend routine use of PMRT unless there are additional adverse features. 8 However, the indication and frequency of PMRT use varies significantly between institutions, and many investigators have identified various risk factors of LRR including young age (eg, ≤45 years), 20 , 21 large tumor size (eg, T2 or >3 cm), 11 , 21 LN ratio (eg, >15%–25%), 20 , 22 24 ER-status, 20 , 25 lymphovascular invasion, 25 , 26 extranodal extension, a medially located tumor, 20 inadequate axillary surgery, 11 and an earlier treatment era (eg, before 1997). 11 However, our results suggest that a risk-adaptive approach should be considered based on overall recurrence risk rather than LRR risk.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative diagnosis of axillary metastasis provides important prognostic information and influences decisions on neoadjuvant chemotherapy and the need for more extensive staging 4 . The presence of a metastatic axillary lymph node is also an important factor in the planning of postmastectomy radiotherapy, and consequently may affect reconstructive options 5 . In addition, this approach has been shown to be a cost-effective measure 6,7 .…”
Section: Introductionmentioning
confidence: 99%